ETNOMATEMATIKA PADA PEMBUATAN PERALATAN DAPUR DI KALIBARU BANYUWANGI SEBAGAI BAHAN AJAR SISWA - Arifin, Achmad Zainul; Sunardi, S; Monalisa, Lioni Anka (Department of Mathematics Education , University of Jember, 2018)
Abstract. Ethnomatematics is the mathematics that is applied by a group of culture unconsciously. The study is conducted at Kalibaru Banyuwangi. The aim of the study is to to describe ethnomatematics and to make a pack of test questions concerning to ethnomatematics on kitchen equipment craftsmen. The type of this research is qualitative with the ethnographic approach and two subject research. Calculating activity appears when determining the length and width of a body with a certain size, determining the height of the filter location, determining the size of the length for the base and lid, making the net cover, determining the volume of parts, determining wages, and making certain diameters. Measuring activity arises when measuring the location of the filter's height, measuring the length and width of the casing, measuring the length of the radius of the base and lid, and measuring the length of the wire. Designing activity arises when the craftsman makes a ruler, makes a filter hole, makes the nets close, and emerge mathematical concept about two-dimentional figure and three-dimentional figure. Making student teaching materials in the form of a package of test questions with the topic of ethnomatematics on craftsmen in the making of dandang with material to construct curved side spaces. Keywords: ethnomatematics. kitchen utensils, student teaching materials